MANAJEMEN TATA USAHA DALAM MENINGKATKAN PELAYANAN ADMINISTRASI DI SMAI PUJER BONDOWOSO - Mukarromah, Luluk; Heridianto, Heridianto (IHTIROM : Jurnal Manajemen Pendidikan Islam, 2024)
Abstract: This study aims to determine the concept of mail management and archive management at SMAI Pujer Bondowoso. The method used by researchers is a descriptive qualitative method. Data collection techniques are observation, interviews and documentation. While data management and data analysis techniques are data collection, data reduction, data presentation and conclusions. The results of the study showed that the management of correspondence at SMAI Pujer Bondowoso was quite good starting from; first, preparing human resources (HR); secondly, the receipt of incoming mail centrally; and third, outgoing mail management using expedition books. Meanwhile, archive management by sorting personnel data and then digitizing all school documents so that archives are better and more organized.